Money Wage Cuts in Relation to Unemployment - Somers, H. M. (Review of Economic Studies, 1939)
Journal Article Money Wage Cuts in Relation to Unemployment Get access H. M. Somers H. M. Somers Berkeley, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 2, February 1939, Pages 161–163, https://doi.org/10.2307/2967399 Published: 01 February 1939